2022
DOI: 10.1101/2022.02.28.482311
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Levels of p53 expression determine the competitive ability of embryonic stem cells during the onset of differentiation

Abstract: During development, the rate of tissue growth is determined by the relative balance of cell division and cell death. Cell competition is a fitness quality control mechanism that contributes to this balance by eliminating viable cells that are less-fit than their neighbours. What mutations confer cells with a competitive advantage or the dynamics of the interactions between winner and loser cells are not well understood. Here, we show that embryonic cells lacking the tumour suppressor p53 are super-competitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 48 publications
(65 reference statements)
3
12
0
Order By: Relevance
“…In some studies it was reported that in naive conditions p53 -/- cells behave as losers instead of winners [ 41 ]. In agreement with Montero and colleagues [ 23 ], we found that in 2i conditions, p53 -/- cells do not show any competitive advantage or disadvantage with respect to WT cells ( Fig 7P ). Interestingly, in naive conditions, WT and p53 -/- ESCs show a similar and small proportion of cells with activated Caspase 3 ( Fig 7Q ) and showed no differences in mitotic index ( Fig 7R ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In some studies it was reported that in naive conditions p53 -/- cells behave as losers instead of winners [ 41 ]. In agreement with Montero and colleagues [ 23 ], we found that in 2i conditions, p53 -/- cells do not show any competitive advantage or disadvantage with respect to WT cells ( Fig 7P ). Interestingly, in naive conditions, WT and p53 -/- ESCs show a similar and small proportion of cells with activated Caspase 3 ( Fig 7Q ) and showed no differences in mitotic index ( Fig 7R ).…”
Section: Resultssupporting
confidence: 93%
“…Previous reports showed that CC driven by different pathways does not take place in naive pluripotent cells [ 5 , 20 , 23 ]. In some studies it was reported that in naive conditions p53 -/- cells behave as losers instead of winners [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, cell competition is primarily dependent on short-range interactions between neighbors 36,42,47 , and our data suggest this is the same for Myc-and p53-mediated competitive interactions between aneuploid and diploid hESCs. But it is unknown how relative differences in cell fitness are communicated between neighbors to affect their fate.…”
Section: Discussionsupporting
confidence: 51%
“…When these cells are injected into the early mouse embryo to create a chimera, they show enhanced competitive abilities and are not eliminated from the population. The mTOR pathway, responsible for aspects of cell competition, was shown to be under the control of p53 in this context, and the removal of p53 activity is able to create ‘super-competitor’ cells [ 29 , 30 ]. Similarly, cMyc protein levels correlate with competitiveness, and over-expression is able to direct the elimination of otherwise healthy cells from the population [ 31 ].…”
Section: Cell Addition As An Essential Tool In Experimental Embryologymentioning
confidence: 99%